Reliability-based maintenance scheduling of power circuit breakers for overhead distribution feeders - Melendres, Jose Mari P. (2001)
Maintenance policies are established with the objective of reducing forced outages due to equipment failures, mitigate its consequences and improve the availability and reliability of its plant physical assets. These preventive maintenance are scheduled to conduct maintenance activities at the right time and frequency. A new technique in establishing maintenance schedules is developed in this study using the probabilistic reliability models of Power Circuit Breakers (PCBs), the expected fault magnitude in the feeders, and the accumulated interrupting capacity of the breaker. The reliability analysis conducted for power circuit breakers used in overhead radial feeders of an electric distribution utility had shown that the power circuit breakers under a time-based maintenance scheduling program were failing at random. On the other hand, the breakers exhibited an increasing hazard rate from the point of view of tripping operations, i.e., the probability of failure increases as the breaker tripping operations to interrupt line faults increases. The proposed method was implemented in a computer program and the method, as applied in a distribution system, results in an appropriate and effective maintenance schedule of PCBs.